An examination of student bullying tendencies in West Sumatera, Indonesia - Yeni Karneli; Edi Purwanta; Mohd Suhadi Bin Mohamed Sidik; Miftahul Fikri; Afdal Afdal; Firman Firman (Jurnal Cakrawala Pendidikan, 2023)
This study aims to examine bullying tendencies among students in Indonesia. A sample of 689 male and female students was selected using a simple random sampling technique. Data were collected through the Bullying Behavior Tendency Scale (BBTS), which consisted of 45 questions using a Likert scale, and were analyzed descriptively. The results showed that the bullying tendencies were in a low category. However, it was discovered that 32.08, 4.06, and 0.87% of students were in the moderate, high, and very high categories, respectively. Additionally, it was observed that there are significant differences in bullying behavior between male and female students. These results provide a basis for understanding the role of school counseling services in reducing bullying behavior which is prevalent and can cause trauma. Therefore, it is essential to implement preventive programs to address the tendencies of some students engaging in this act at school.